Talking to Children about Disasters - Suzanna Smith (EDIS, 2012)
“Natural disasters, refugees displaced from their homes, loss of life . . . even for adults, these tragic events are difficult to understand. Children, too, may find these incidents especially troubling. Adults can help young people make sense of disasters and deal with their feelings by following a few guidelines.” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, September 2012.